Information management in interactive and non-interactive suspenseful storytelling - Pablo Delatorre; Carlos León; Alberto Salguero; Manuel Palomo-Duarte; Pablo Gervás (Connection Science)
Suspense is one key feature in modern storytelling. One of the mechanisms to deliver a suspenseful experience to an audience is by means of controlling the information provided. The media, however, has a very strong impact on what kind of information can be delivered and how. Moreover, modern storytelling is usually conveyed interactively, in such a way that the audience is also part of the story. In this paper, we experiment and analyse the different impact of information management in interactive and non-interactive storytelling. We report on an experiment measuring the reported perceived amusement in interactive and non-interactive versions of a potentially suspenseful story, and we provide evidence that a passive, non-interactive audience usually prefers less information than an active interactive audience. The study provides informed insight on how these results could be used in real scenarios to deliver appropriate levels of information to enhance the perception of suspense.